GODLESSNESS Vs. GOODLINESS: AYN RAND’S ART OF CHARACTERIZATION - PRITI NAYAK (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2021)
Characterization in fiction is undoubtedly the combination of philosophical thoughts and ideas of the writer and therefore in order to study the vision of life reflected in the fiction of Ayn Rand, one cannot afford to skip devoting oneself to an analytical and comprehensive study of the characters in Rand’s fiction. The ‘Godless’ refers to those characters who give in or blindly accept the evil designs of the society and the state – the juggernaut of collectivism, socialism, statism, mysticism, altruism that ruthlessly crushes the good – the ‘goodliness’ in the people, of the people and for the people. And out of the conflict between this ‘godlessness’ and ‘goodliness’ emerge the Randianness – the vision of life that Rand desires and dares to portray through her characters – with a focus on individualism, integrity, rational self-interest, reason and happiness as the ultimate virtue.